Mechanisms of enhancement of light emission in nanostructures of II-VI compounds doped with manganese: Структура и свойства полупроводников с переходными элементами - Godlewski, M.; Yatsunenko, S.; Ivanov, V.Yu.; Drozdowicz-Tomsia, K.; Goldys, E.M.; Phillips, M.R.; Klar, P.J.; Heimbrodt, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Intra-shell transitions of transition metal and rare earth ions are parity forbidden processes. For Mn2+ ions this is also a spin forbidden process, i.e., light emission should be inefficient. Surprisingly, it was reported that in nanostructures of ZnMnS the 4T1 to 6A1 intra-shell transition of Mn2+ results in a bright photoluminescence characterized by a short PL decay time. The model of a quantum confined atom was introduced to explain the observed experimental results. It was later claimed that this model is incorrect. Based on the results of our photoluminescence, photoluminescence kinetics, time-resolved photoluminescence, electron spin resonance and optically detected magnetic resonance investigations we confirm photoluminescence enhancement and decrease of photoluminescence lifetime and relate these effects to spin dependent magnetic interactions between localized spins of Mn2+ ions and spins/magnetic moments of free carriers. This mechanism is active in both bulk and in low-dimensional structures, but is significantly enhanced in nanostructure samples.